Pengaruh Harga, Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Mixue Ice Cream dan Tea Nusukan Surakarta - Irfan Rizqi Pangestu; Retno Susanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Consumer purchasing decisions are a process in consumer behavior where consumers have taken action to make a purchase after searching and understanding information. The increase in sales occurred at Mixue Ice Cream & Tea Nusukan, where this increase was one of the impacts of consumer decisions. This research purpose to analyze factors that influence purchasing decisions, including price, promotion and service quality at Mixue Ice Cream & Tea Nusukan. The population in this research are consumers who make purchases at Ice Cream & Tea Nusukan. The samples obtained were 100 people using Leedy technique calculations. The sampling technique used was accidental sampling with data collection techniques using questionnaires. Data analysis techniques in this research use validity tests, reliability tests, classical assumption tests, descriptive analysis, multiple linear regression analysis, t test, F test and coefficient of determination test. The results of the analysis stated that all questionnaire items as research instruments were valid and reliabel, as well as the classical assumption tests, including the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test, all variabels were declared to have passed the classical assumption test. Multiple linear regression analysis obtained that all regression coefficients were positive with the equation Y= 3.809 + 0.134X1 + 0.365X2 + 0.230X3 + e which means that variabels X1 (price), X2 (promotion) and X3 (service quality) on Mixue Ice Cream & Tea Nusukan. Hypothesis testing shows that price has a significant effect on purchasing decisions at Mixue Ice Cream & Tea Nusukan. Promotions have a significant influence on purchasing decisions for Mixue Ice Cream & Tea Nusukan. Service quality has a significant influence on purchasing decisions at Mixue Ice Cream & Tea Nusukan. The F test states that the research model for the influence of the independent variabel on the dependent variabel is correct. The coefficient of determination test shows that price, promotion and service quality are able to explain purchasing decisions by 42.6%.